Supply chain management in the era of fast clockspeed emergence of new logistical technologies - Ng, Siow Yun (2017)
In recent years, it is observed that with technological advancement and increased competition in the market, the clockspeed of most industries is increasing. Product lifecycles are getting shorter, the rate of product obsolescence is increasing and customers are also becoming harder to please. They demand for greater product variety and are less tolerant to delay. In addition, the greater demand volatility and uncertainty are also making it harder for companies to forecast their demand accurately. To make matters worse, it is no longer about how well companies compete as a single organisation, but about how well can they manage their supply chain. Thus, there is a greater need for companies to adapt and align their supply chain in response to the aforementioned challenges.